2011
DOI: 10.1530/rep-10-0493
|View full text |Cite
|
Sign up to set email alerts
|

A dense network of dendritic cells populates the murine epididymis

Abstract: One of the most intriguing aspects of male reproductive physiology is the ability to generate spermatogenic cells - which are “foreign” to the host - without triggering immune activation. After leaving the testis, spermatozoa enter the epididymis where they mature and are stored. We report here a previously unrecognized dense network of dendritic cells located at the base of the epididymal epithelium. This network was detected in transgenic mice expressing CD11c-EYFP and CX3CR1-GFP reporters. Epididymal dendri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
189
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 105 publications
(205 citation statements)
references
References 76 publications
(105 reference statements)
16
189
0
Order By: Relevance
“…A recent study has found a network of dendritic cells in the mouse epididymis (39). These immune cells are thought to constitute the frontline of the epididymal defense against invading microbes (35).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study has found a network of dendritic cells in the mouse epididymis (39). These immune cells are thought to constitute the frontline of the epididymal defense against invading microbes (35).…”
Section: Discussionmentioning
confidence: 99%
“…Cells with dendritic phenotype forming a dense network have been described at the base of the mouse epididymal epithelium, sending cytoplasmic extensions between epithelial cells towards the lumen. 94 NK and NKT cells, innate immune cells participating in the elimination phase of tumour immunoediting, 89 have not been studied in the epididymis, other than in its associated adipose tissue. In contrast to ,2% of all lymphocytes in blood or lymph nodes being NK or NKT cells, these cells account for ,12% in inguinal fat and exceed 30% in the epididymal fat pad.…”
Section: Endogenous Barriers To Tumour Formation: Immunosurveillancementioning
confidence: 99%
“…Our previous work further suggested that the basal compartment of the epithelium might, in fact, be more complex than generally portrayed in the literature. Indeed, using transgenic mouse models expressing fluorescent proteins under the control of the CD11c (integrin alpha X chain) and CX3CR1 (fractalkine receptor), two markers of mononuclear phagocytes (MPs), we described a very abundant and heterogeneous population of immune cells (macrophages and dendritic cells) in the peritubular and interstitial compartments of the mouse epididymis [48]. Owing to the notorious heterogeneity of the MP system and the long-standing controversy that surrounds the respective origin, function, and nomenclature of macrophages and dendritic cells [49][50][51][52][53], we now prefer to use the less restrictive term ''epididymal mononuclear phagocytes'' (eMPs) to describe these cells.…”
Section: Introductionmentioning
confidence: 99%